2019
DOI: 10.4314/ijbcs.v12i6.9
|View full text |Cite
|
Sign up to set email alerts
|

Habitat use in wild pygmy hippopotamus (<i>Choeropsis liberiensis</i>) in Taï National Park, Côte d’Ivoire

Abstract: The Pygmy Hippopotamus (PH) Choeropsis liberiensis (Morton, 1849) is a rare and cryptic mammal. Considered as an endangered species by International Union for Conservation of Nature in 2017, the main threats to PH are the fragmentation of its habitat, the forest, and hunting. Its population has greatly diminished during the last two decades from nearly 15,000 individuals to an estimated number of approximately 3,000 individuals today. Studies of this species' ecology in the wild are rare. This study focuses on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Other studies have already suggested that the TNP would harbour the largest wild population of the species ( Roth et al, 2004 ). Also, their presence can be explained by the abundance of rivers in the park as it is known to live near marshy areas (presence of water and moist soil), in shallows and rivers ( Bogui et al, 2016 ; Ouattara et al, 2018 ). Among the four species, pygmy hippopotamus is the one that reacted the most to the CTs and more than half of the data had to be deleted for the abundance determination as they often showed inspection behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have already suggested that the TNP would harbour the largest wild population of the species ( Roth et al, 2004 ). Also, their presence can be explained by the abundance of rivers in the park as it is known to live near marshy areas (presence of water and moist soil), in shallows and rivers ( Bogui et al, 2016 ; Ouattara et al, 2018 ). Among the four species, pygmy hippopotamus is the one that reacted the most to the CTs and more than half of the data had to be deleted for the abundance determination as they often showed inspection behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis focused on 'declared' protected areas according to the United Nations Environment Programme -World Conservation Monitoring Centre (UNEP-WCMC & IUCN 2021). There are 87 protected areas covering 30 669 km 2 that are partially or totally located inside the pygmy hippopotamus's range (UNEP-WCMC & IUCN 2021), and pygmy hippopotami are known to inhabit them (Roth et al 2004, Collen et al 2011, Garteh 2013, Conway et al 2015, Bogui et al 2016, Hillers et al 2017, Ouattara et al 2018.…”
Section: Protected Areas Inside Pygmy Hippopotamus Distributionmentioning
confidence: 99%